Some renal function parameters in individuals with metabolic syndrome - A. Alkataan, Mohammad (Tikrit Journal of Pharmaceutical Sciences, 2023)
Metabolic syndrome (MS), a cluster of risk factors for cardiovascular diseases. This syndrome characterized by: Insulin resistance, hyperinsulinemia, abdominal obesity, elevated blood pressure, lipid abnormalities and low grade inflammatory state. There are growing data demonstrated the relation between MS and renal impairment, these data revealed that individual with MS at higher risk to develop chronic kidney disease. (a) To determined the changes in renal function parameters in MS individuals.(b) determine the effect of age, sex and BMI on the measured parameters . This study was conducted during period from January to September 2011. Fifty apparently healthy individual (30 male and 20 female) were included in this work as control with age range 25±6.3 years, BMI range 21± 3.7 Kg/m2 and weight range 55± 3.9 Kg and another fifty individual(30 male and 20 female) were selected to have at least three of the WHO criteria of MS. Data were presented as mean ± SD , 2-sample t-Test was used to show the significance changes between the two groups. The effect of age and BMI on measured parameters were determined using Person - correlation. This study revealed that MS individual shows a significant increase in SFG,TC,TG, B.Urea, S.Cr and U.Sp-G when compared to those of the controls, while HDL-C and e-GFR shows significant reduction when compared to those of control table 1. In both group e-GFR significantly correlated to individual weight ( r =0.02), BMI (r =.0.075).SFG significantly correlated to B.Urea, S.Cr., e-GFR and U.Sp-G in MS individual (r = 0.03) but not in control group. In conclusion: MS individual show significant changes in renal function that may related to higher susaptability of this group to developing renal diseases